Risk of infection according to the gamma globulin level in the 100 days following allogeneic stem cell transplantations. (18th July 2021) - Lacombe, Valentin; Nunes Gomes, Christopher; Robin, Jean‐Baptiste; Thépot, Sylvain; François, Sylvie; Cottin, Laurane; Ugo, Valérie; Dieu, Xavier; Abgueguen, Pierre; Daniel, Valérie; Giltat, Aurélien; Hunault, Mathilde; et al.
Abstract: Background: Immunoglobulin replacement therapy is recommended in case of severe hypogammaglobulinemia after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). However, the supposed increased risk of infection in case of hypogammaglobulinemia has not been confirmed in allo‐HSCT. In this study, we assessed the relationship between the gamma globulin level and the risk of infection during the 100 days following the allo‐HSCT. Methods: We gathered the weekly laboratory tests from day 7 to day 100 of 76 allograft patients, giving a total of 1 044 tests. 130 infections were documented clinically, by imaging, or microbiologically. Results: Average gamma globulin levels between D‐7 and D100 did not differ between patients with or without infection (642 ± 232 and 671 ± 246 mg/dL, respectively, P  = .65). Gamma globulin level <400 mg/dl was not associated with the occurrence of infection between the test studied and the next one (aOR 1.33 [0.84‐2.15], P  = .24). The gamma globulin level was not predictive of bacterial or fungal infections (AUC 0.54 [95%CI: 0.47‐0.61]) nor of viral reactivations (AUC 0.51 [95%CI: 0.43‐0.60]). Conclusions: This confirmed that the humoral deficiency is a minor part of the immune deficiency in the 100 days post‐transplant. This questions the relevance of the indications of immunoglobulin substitution during this period.